The Effect of Tourist Attractions on the Progress of the Sipinsur Geosite Tourism Object in Pearung Tourism Village, Humbang Hasundutan Regency in 2024 - Sianturi, Winda; Sitio, Robert Juni Tua; Fero, David; Nadeak, Tio RJ; Sitorus, Masniar Hernawaty (Formosa Journal of Applied Sciences, 2024)
This study aims to determine the positive and significant influence of tourist attractions (x) on the progress of tourist attractions (y) Geosite Sipinsur in Pearung Tourism Village, Humbang Hasundutan Regency in 2024. This research uses a quantitative approach by distributing questionnaires to 96 respondents by accidential sampling. To determine the answer score on the questionnaire which will be tested for validity and reliability using a Likert scale. The data analysis technique used is descriptive statistical analysis, Pearson Product Moment correlation, determination coefficient test and simple linear regression analysis. Based on the results of descriptive statistical analysis, the influence of tourist attractions on the progress of tourist attractions is in a good category, with an average of 4.5449 at the interval of the category very advanced. The test results of the correlation coefficient (r) = 0.586 with a sufficient category and compared with r table = 0.200, where r count> r table (0.586> 0.200) it can be said to be significant and the hypothesis is accepted.